Penerapan Media Interaktif dengan Model Discovery Learning pada Pembelajaran Tematik untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik Kelas VI SDN 62 Lebong - Gita Riskyana; Dalifa; Feri Noperman (JURIDIKDAS, 2022)
This study aims to describe the application of interactive media in discovery learning (DL) model in thematic learning, describe the activity and learning outcomes of learners with interactive media using DL model in learning in sixth grade VI SDN 62 Lebong. This type of research is classroom action research. The subjects of this study were teachers and students of sixth grade SDN 62 Lebong the research instruments used were observation sheets and evaluation tests. Observation data analysis techniques using the formula average score, highest score, lowest score, difference score and range of values for each criterion while the analysis of test data using the formula to find the average value and the percentage of completion of learning. The application of learning using the learning model Discovery Learning with interactive media runs smoothly and can improve the liveliness and learning outcomes of students proved by the results of the study showed the liveliness and learning outcomes of students in the first cycle of good predicate and increased in the second cycle with the predicate very good . Thus it can be concluded that learning with interactive media with discovery learning model can increase the liveliness and learning outcomes of students in thematic learning in sixth grade SDN 62 Lebong